Preserving the Original Layout of Ancient Chinese Texts Using HTML5: Using Shuowen Jiezi as an Example. - Yap, Cheah-Shen; McIlwaine, Ian (International Journal of Humanities & Arts Computing: A Journal of Digital Humanities)
We have developed a software platform for converting the Chinese classics into a digital format which the original layout is preserved. This method of conversion allows those that are not experts in classical Chinese literature, even those that do not understand Chinese, to partake in the proof-reading process. Since this kind of application involves complicated manipulation of 2D graphics, in the past, we have no choice but writing a native desktop program, with the introduction of CANVAS tag to the HTML 5 standards, we are able to move our code from desktop to browser without any plug-in or JAVA applet. The cost of cross-platform development and maintenance is greatly reduced. In order to clarify the various elements involved in the conversion and proof-reading process, we will use Duan Yu Cai's compilation of the Shuowen Jiezi as an example throughout this paper.